2018
DOI: 10.1016/j.echo.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Longitudinal Strain Reproducibility Using Vendor-Dependent and Vendor-Independent Software

Abstract: Global RVLS values between VSS systems are not significantly different but may differ slightly from VIS. When comparing regional strain between VSS and VIS analyses, there is widespread variability without clear systematic differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 23 publications
3
23
1
Order By: Relevance
“…In addition, speckle‐tracking RV strain also has the unique advantage of being angle‐independent, and able to measure the intrinsic myocardium deformation 13 . An issue of using RV strain is the different reference values generated by the software package from different vendors; one should be cautious when comparing RV strain data from different studies 13,48,49 . The ease of performance for sonographers comparing all four modalities in descending order are TAPSE, Sʹ, FAC, and RV strain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, speckle‐tracking RV strain also has the unique advantage of being angle‐independent, and able to measure the intrinsic myocardium deformation 13 . An issue of using RV strain is the different reference values generated by the software package from different vendors; one should be cautious when comparing RV strain data from different studies 13,48,49 . The ease of performance for sonographers comparing all four modalities in descending order are TAPSE, Sʹ, FAC, and RV strain.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that RVLS associated with negative outcomes in the diseases affecting RV function [25,26], so it could be used as a standard and reproducible method to evaluate RV function [22].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a wide agreement regarding normal values is lacking and it seemed that it depends on the kind of machine and vendors as we can see in different articles [22].…”
Section: Role Of Speckle Tracking Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of similar design focusing on LV and RV strain [23], the authors found there was good reproducibility for global longitudinal strain, but only moderate reproducibility for circumferential strain and poor reproducibility for radial strain when comparing LV strain, and good reproducibility across different ultrasound platforms and software packages when comparing the RV strain [24]. The main contractile direction of the left atrium is longitudinal [25], and it is reasonable to posit that Sct had a smaller bias and CoV across different ultrasound platforms and software packages than Sr and Scd.…”
Section: Discussionmentioning
confidence: 99%